A story told by a single nanoparticle in the body fluid: demonstration of dissolution-reprecipitation of nanocrystals in a biological system. (September 2015) - Wu, Cheng-Yeu; Young, David; Martel, Jan; Young, John D
Aim: Analysis of the chemical composition of mineral particles found in the body is critical to understand the formation and effects of these entities in vivo . Yet, the possibility that biological fluids may modulate particle composition over time has not been examined.Materials & methods:  Mineralo-organic nanoparticles similar to the ones that spontaneously form in human tissues were analyzed using electron microscopy, spectroscopy and proteomic analyses. Results:  We show that the mineralo-organic nanoparticles assimilate various ions and minerals during incubation in ionic solutions simulating body fluids. The particles undergo dissolution-reprecipitation reactions that affect the final protein composition of the particles.Conclusion: The reactions occurring at the mineral-water interface therefore modulate the ionic and organic composition of mineral nanoparticles formed in biological fluids, producing changes that may alter the effects of mineral particles and stones in vivo .